Heavy metal concentrations in sugar beet fields and sugar beet in Finland - Erjala, Matti; Erviö, Raimo (fi, 1994)
The heavy metal (Cd, Cr and Pb) study of Finnish sugar beet fields and sugar beet of 1993 shows that the sugar beet fields are as clean as any other surrounding fields from heavy metals within the same region in Finland. The heavy amelioration of sugar beet fields has not had any direct negative influence on the heavy metal concentrations in the soil....
moniste, 1995 mahdollisesti julkaisu